ANALISIS DAMPAK HARGA DAN VOLUME PERDAGANGAN TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR PARIWISATA DI INDONESIA PERIODE SEBELUM DAN SELAMA COVID-19 - Alliya, Himmatul; Dwi Budi Santoso (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Indonesia has many tourist destinations visited by local and foreign residents. So, Indonesia has great prospects for the tourism sector. However, Covid-19 caused tourism performance to decline as a result of government policy (PPKM). Covid-19 as an investment risk can undermine investor confidence in tourism sector stocks so that stock returns will be affected. This research aims to compare the influence of price and trading volume on tourism company stock returns before and during Covid-19 in Indonesia. This research uses the Vector Auto Regression method. The data used is a time series with a monthly time period from 2017 to 2022. This research found that the similarity of results in the period before and during Covid-19 shows that share prices are an important factor for low, medium and high return companies so that companies need to maintain market prices to be balanced. Low return companies are more sensitive to market shocks so they must be careful about risks. Trading volume is important for high return companies so it needs to be increased so that transactions also increase.